PENERAPAN PENERAPAN SISTEM LAPORAN KEUANGAN DAN PERPAJAKAN BERBASIS MICROSOFT EXCEL DALAM PENENTUAN TARGET LABA PADA POLJAMTECH: PENERAPAN SISTEM LAPORAN KEUANGAN DAN PERPAJAKAN BERBASIS MICROSOFT EXCEL DALAM PENENTUAN TARGET LABA PADA POLJAMTECH - Anjeli Penisa Putri (Journal of Applied Accounting And Business, 2026)
This study aims to implement a Microsoft Excel-based financial and tax reporting system in determining profit targets at Jambi Polytechnic (Poljamtech). Poljamtech is a business unit engaged in project sales and does not yet have a systematic financial and tax reporting system, so financial management and tax calculations are not optimal. This study uses a qualitative approach with descriptive methods through observation, interviews, and documentation. The results show that the implementation of a Microsoft Excel-based financial reporting system is able to accommodate transaction recording, preparation of profit and loss reports, balance sheets, and calculation of 0.5% Income Tax (PPh) more accurately and efficiently. This system helps Poljamtech in analyzing the income and costs of each project, determining net profit after tax, and setting more realistic and measurable profit targets. Thus, the Microsoft Excel-based financial and tax reporting system can improve transparency, calculation accuracy, and support financial decision-making at Poljamtech in a sustainable manner.